Predictors of female lecturers reproductive health behaviour in tertiary institutions in Nigeria (2016)
Women reproductive health behaviour (RHB) has generated a lot of interest from researchers across many disciplines because of complications on women health generally. Previous studies on women's RHB had focused on various categories of women and teenagers leading to a gap in literature on women in the tertiary institutions. This study, therefore, examined the extent to which cultural norms/religious belief, peer influence and mass media exposure influenced the RHB of female lecturers in tertiary institutions in South western Nigeria. The survey research design was adopted. The purposive sampling technique was used to 540 academic workers from thirteen tertiary institutions in South western Nigeria. Two instruments were used: RHB Scale (r-0.81) and RHB Determinants Scale with sub-scales, cultural/religious belief (r=0.83), mass media (r=0.75), and peer influence (r=0.71). Three hypotheses were tested at 0.05 level of significance to determine the RHB of female workers. Pearson product moment correlation and content analysis was used to analyse data collected through the questionnaire form the respondents. Seventy-five percent of respondents exhibited good RHB. Their significant strength of relationships with RHB was ranked: religious/cultural belief (r=0. .066); mass media exposure (r=0.070), and peer influence (r=-0.602).Mass media exposure, cultural norms/religious belief and peer influence strongly predicted reproductive health behaviour of female lecturers in sampled tertiary institutions. Improvement in the reproductive health behaviour among tertiary institutions female lectures calls for government to encourage and motivate women having two or more children to adopt family planning through mass media messages